Miss Leavitt's stars : the untold story of the woman who discovered how to measure the universe - Johnson, George, 1952 January 20- (New York : W.W. Norton, 2005)
How big is the universe? In the early twentieth century, scientists took sides. One held that the entire universe was contained in the Milky Way galaxy; their champion was the strong-willed astronomer Harlow Shapley. Another camp believed that the universe was so vast that the Milky Way was just one galaxy among billions--the view that would prevail, proven by the equally headstrong Edwin Hubble. Almost forgotten is the Harvard Observatory Computer--a human number cruncher hired to calculate the positions and luminosities of stars in astronomical photographs--who found the key to the mystery. Radcliffe-educated Henrietta Swan Leavitt, fighting ill health and progressive deafness, stumbled upon a new law that allowed astronomers to use variable stars--those whose brightness rhythmically changes--as a cosmic yardstick. This book is both an account of how we measure the universe, and the moving story of a neglected genius.--From publisher description.
Includes bibliographical references (p. 149-150) and index.
Keywords: Leavitt, Henrietta Swan, -- 1868-1921.; Harvard College Observatory -- History; Astrometry -- History; Women astronomers -- United States -- Biography; Astronomical photometry; Astronomy -- United States -- History -- 20th century